Virus taxonomy : classification and nomenclature of viruses : eighth report of the International Committee on the Taxonomy of Viruses - Fauquet, C.; ScienceDirect eBooks (San Diego, Calif. ; London : Elsevier Academic Press, 2005)
This is the standard and definitive reference for virus taxonomy, generated by the ICTV approximately every 3 years. The VIII ICTV Virus Taxonomy Report provides information on 3 orders of viruses, 73 families, 9 subfamilies, 287 genera and 1938 virus species, illustrated by more than 429 pictures and diagrams, most of them in color. * The standard official ITCV reference for virus taxonomy and nomenclature, compiling data from 500 international experts * Covers over 6000 recognized viruses, organized by family with diagrams of genome organization and virus replication cycle * Provides data on the phylogenic relationships between viruses belonging to the same or different taxa * Now includes information about the qualitative and quantitative relationships between virus sequences.
pt. I. Introduction to universal virus taxonomy -- pt. II. The viruses -- A glossary of abbreviations and terms -- Taxa listed by nucleic acid and size of the genome -- The virus diagrams -- The virus particle structures -- The order of presentation of the viruses -- The double stranded DNA viruses -- The single stranded DNA viruses -- The DNA and RNA reverse transcribing viruses -- The double stranded RNA viruses -- The negative sense single stranded RNA viruses -- The positive sense single stranded RNA viruses -- The unassigned viruses -- The subviral agents -- pt. III. The International Committee on Taxonomy of Viruses -- Officers and members of the ICTV, 1999-2002 -- The statutes of the ICTV, 1998 -- The code of virus classification and nomenclature, 1998 -- pt. IV. Indexes -- Virus index -- Taxonomic index.
Includes bibliographical references and index.
Print version record.
Elsevier
Keywords: Viruses -- Classification; Virus -- Classification; Virus -- Nomenclature; Viruses; Viruses -- classification -- Classification; Virology; Electronic books